Integrasi Sistem Informasi Pemerintah di Bapenda Palopo - Angrianto, Nurpadilah, Salwa Madani (PT Wahana Global Education, 2025)
This research explores the integration of the Srikandi (Integrated Dynamic Archiving Information System) applicationwith existing digital systems at the Regional Revenue Agency (Bapenda) of Palopo. Srikandi, developed under Indonesia’s national electronic-based government system (SPBE), is designed to manage state archives and improve the efficiency and accountability of public institutions. However, its implementation in regional offices presents several challenges, including limitations in technical infrastructure, lack of human resource capacity, and incompatibility between systems. This study aims to identify the current condition of system integration, determine organizational readiness, and propose an effective integration model for Bapenda Palopo. The methodology used is a qualitative-descriptive approach, combining field observations, documentation studies, and interviews with key stakeholders. Results show partial implementation of Srikandi, hindered by limited infrastructure and system incompatibility. Organizational support exists but is constrained by a lack of technical expertise and insufficient training. Based on the findings, this paper proposes a step-by-step integration model emphasizing change management, technical alignment, and capacity building. The study contributes to the understanding of how government digital transformation can be localized and adapted to regional conditions. It also provides recommendations to improve interoperability and stakeholder engagement in future integrations. This work is significant for policymakers, IT developers, and local governments aiming to improve public service delivery through effective digital archiving systems.